Adhesive suitable for storage device electrode, adhesive solution, storage device electrode slurry, storage device electrode and storage device

By using water-soluble resin powder with suitable average particle size and roundness, the gel-like agglomeration problem of the resin powder during dissolution is solved, and the uniformity and high performance of the electrode are achieved.

CN115210914BActive Publication Date: 2025-04-29KURARAY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202180021316.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-16
Filing Date
2021-03-12
Publication Date
2025-04-29
Estimated Expiration
2041-03-12

AI Technical Summary

Technical Problem

In the prior art, water-soluble resin powder is prone to gel-like agglomeration when dissolved, resulting in poor electrode uniformity and making it difficult to form electrodes with low resistance and high discharge capacity.

Method used

A water-soluble resin powder with an average particle size of 100~2,000μm was used, and the rounding degree was made between 0.1~0.8 by rounding treatment, ensuring that the contact area between particles was small and it was difficult to fusion and aggregation.

Benefits of technology

It effectively avoids gel-like agglomeration of resin powder when dissolved, ensures the uniformity of the electrode, and improves the low resistance and high discharge capacity performance of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115210914B_ABST
    Figure CN115210914B_ABST
Patent Text Reader

Abstract

Provided is an adhesive that is less likely to form gel-like lumps when the adhesive is dissolved and that can be used for storage device electrodes to form uniform electrodes that have low resistance and high discharge capacity. Disclosed is an adhesive that includes a water-soluble resin powder, the water-soluble resin powder being composed of particles having an average particle size of 100 to 2,000 μm, and for 50 particles randomly selected from particles having a particle size of 100 to 1,000 μm contained in the water-soluble resin powder, the average value PA of the roundness P of each particle represented by the following formula (1) is 0.1 to 0.8, [wherein, r i is the radius of curvature of each corner of the particle, R is the radius of the largest inscribed circle of the particle, and N is the number of corners of the particle. When the number of corners of the particle is 9 or more, the radii of curvature of the 8 corners are used in ascending order of the radius of curvature, and N is set to 8].
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This patent application claims priority under the Paris Convention based on Japanese Patent Application No. 2020-044897 (filing date: March 16, 2020), which is hereby incorporated by reference in its entirety into this specification.

[0002] The present invention relates to an adhesive suitable for an electrical storage device electrode, an adhesive solution, an electrical storage device electrode slurry, an electrical storage device electrode, and an electrical storage device. Background Art

[0003] In recent years, portable terminals such as mobile phones, notebook personal computers, and tablet information terminals have become significantly popular. Portable terminals are required to be more comfortable and portable, and with the rapid advancement of miniaturization, thinning, lightness, and high performance, the batteries used in portable terminals are also required to be miniaturized, thinned, lightened, and high-performance. As a power storage device used in such portable terminals, lithium-ion secondary batteries are mostly used. Non-aqueous electrolyte batteries such as lithium-ion secondary batteries have a positive electrode and a negative electrode arranged via a separator, and have the same characteristics as LiPF. 6 , LiBF 4 The structure is a structure in which these electrodes are housed in a container together with an electrolyte obtained by dissolving a lithium salt such as LiTFSI ((bis(trifluoromethylsulfonyl)imide) lithium) and LiFSI ((bis(fluorosulfonyl)imide) lithium).

[0004] The negative electrode and positive electrode constituting the storage device are usually prepared by dissolving or dispersing a binder and a thickener in water or a solvent, mixing an active material, a conductive aid (conductive agent), etc., into an electrode slurry, applying the slurry onto a current collector, and then drying the water or solvent to solidify the mixture into a mixed layer.

[0005] From the perspective of reducing the load on the environment and the simplicity of the manufacturing device, the trend of using aqueous media in electrode slurries, especially in the manufacture of negative electrodes, is rapidly advancing. As binders used in such aqueous medium electrode slurries, known binders include vinyl alcohol polymers (hereinafter also referred to as "PVA"), acrylic acid and other acrylic polymers, and amide / imide polymers (e.g., Patent Documents 1 and 2).

[0006] On the other hand, in the manufacture of the positive electrode, generally speaking, an electrode slurry using a solvent is used. Examples of the solvent include organic solvents such as N-methyl-2-pyrrolidone, dimethylformamide, N,N-dimethylacetamide, N,N-dimethylmethanesulfonamide, and hexamethylphosphoric triamide. As binders used in such organic solvent electrode slurries, known are vinylidene fluoride polymers, tetrafluoroethylene polymers, fluororubbers, and the like (e.g., Patent Documents 3 and 4).

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 11-250915

[0010] Patent Document 2: Japanese Patent Application Publication No. 2017-59527

[0011] Patent Document 3: Japanese Patent Application Publication No. 2017-107827

[0012] Patent Document 4: Japanese Patent Application Publication No. 2013-37955. Summary of the invention

[0013] Problems to be solved by the invention

[0014] However, in the manufacture of any of the negative electrode and the positive electrode described in Patent Documents 1 to 4, when a slurry (electrode slurry) obtained by mixing a binder, a solvent (water or a solvent) and an active material, a conductive aid (conductive imparting agent), etc. is applied on a current collector to form an electrode, the form of materials such as the binder in the slurry and various conditions in the slurry preparation have an impact, for example, a large number of problems such as those shown below occur.

[0015] When using resin powder as an adhesive, it is necessary to dissolve the resin powder in water or a solvent (N-methyl-2-pyrrolidone (NMP) etc.) in advance. In the case of water-soluble resin powder, the particles constituting the powder fuse in the piping and silo to form agglomerates, and sometimes gel-like lumps are generated during dissolution. If a large amount of an adhesive solution containing gel-like lumps is used to prepare a slurry, it is difficult to disperse the active material in the slurry, and as a result, it is difficult to form an electrode uniformly, and sufficient performance, especially low resistance and high discharge capacity, cannot be obtained. Due to the water solubility and hygroscopicity of the water-soluble resin powder, such agglomerates are easily generated, and gel-like lumps are easily generated during dissolution, especially in an environment with high humidity.

[0016] Therefore, an object of the present invention is to provide an adhesive for a storage device electrode that is less likely to produce gel-like agglomerates when a water-soluble resin powder is dissolved, and that can suitably form a uniform electrode (an electrode with a small deviation in the film thickness of the coated electrode) when used for a storage device electrode, and that has low resistance and high discharge capacity.

[0017] Means for solving problems

[0018] The above-mentioned object is achieved by the present invention including the following suitable modes.

[0019] [1] An adhesive comprising a water-soluble resin powder,

[0020] The water-soluble resin powder is composed of particles with an average particle size of 100 to 2,000 μm.

[0021] For 50 particles randomly selected from particles having a particle size of 100 to 1,000 μm contained in the water-soluble resin powder, the average value PA of the roundness P of each particle represented by the following formula (1) is 0.1 to 0.8,

[0022] [Number 1]

[0023]

[0024] [In formula (1),

[0025] r i is the radius of curvature of each corner of the particle,

[0026] R is the radius of the largest inscribed circle of the particle,

[0027] N is the number of corners a particle has,

[0028] When the number of corners of a particle is 9 or more, the curvature radii of the 8 corners are used in ascending order of curvature radii, and N is set to 8].

[0029] [2] The adhesive according to [1], wherein the water-soluble resin is a vinyl alcohol polymer.

[0030] [3] The adhesive according to [1] or [2], wherein the vinyl alcohol polymer has a viscosity average degree of polymerization of 200 to 5,000 and a saponification degree of 35 to 99.99 mol %.

[0031] [4] The adhesive according to any one of claims 1 to 3, which satisfies the following formula (2):

[0032]

[0033] [In formula (2), PA is the same as defined above, and S is the saponification degree of the vinyl alcohol polymer (mol %)]

[0034] The water-soluble resin powder has an average particle size of 100 to 1,000 μm.

[0035] [5] The adhesive according to any one of [1] to [4], wherein the content of particles having a particle size of 100 to 1,000 μm in the water-soluble resin powder is 50% by mass or more.

[0036] [6] An electrical storage device electrode comprising the binder according to any one of [1] to [5].

[0037] [7] A binder solution for a storage device electrode, comprising the binder according to any one of [1] to [5] and water.

[0038] [8] The binder solution for electrical storage device electrodes according to [7], comprising N-methyl-2-pyrrolidone.

[0039] [9] A slurry for electrical storage device electrodes comprising the binder solution for electrical storage device electrodes according to [7] or [8] and an active material.

[0040]

[10] The electrical storage device electrode slurry according to [9], wherein the content of the binder is 0.1 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the active material.

[0041]

[11] An electrical storage device electrode comprising a solidified body of the electrical storage device electrode slurry according to [9] or

[10] and a current collector.

[0042]

[12] An electric storage device comprising the electric storage device electrode described in

[11] .

[0043]

[13] The method for producing an adhesive according to any one of [1] to [5], comprising:

[0044] A step of obtaining a coarse powder of the water-soluble resin by pulverizing a resin solid containing the water-soluble resin; and

[0045] A step of processing the surfaces of particles constituting the coarse powder.

[0046] Effects of the Invention

[0047] According to the present invention, it is possible to provide an adhesive for storage device electrodes that is less likely to produce gel-like agglomerates when a water-soluble resin powder is dissolved, and when used for storage device electrodes, can suitably form uniform electrodes (electrodes with small deviations in the film thickness of the coated electrodes), and can also provide storage device electrodes having low resistance and high discharge capacity. DETAILED DESCRIPTION

[0048] <Resin powder>

[0049] The adhesive of the present invention comprises a water-soluble resin powder. The powder is composed of particles having an average particle size of 100 to 2,000 μm, and for 50 particles randomly selected from particles having a particle size of 100 to 1,000 μm contained in the water-soluble resin powder, the average value PA of the roundness P of each particle represented by formula (1) (hereinafter also referred to as "average roundness") is 0.1 to 0.8,

[0050] [Number 2]

[0051]

[0052] [In formula (1),

[0053] r i is the radius of curvature of each corner of the particle,

[0054] R is the radius of the largest inscribed circle of the particle,

[0055] N is the number of corners a particle has,

[0056] When the number of corners of a particle is 9 or more, the curvature radii of the 8 corners are used in ascending order of curvature radii, and N is set to 8].

[0057] As described above, the water-soluble resin powder contained in the adhesive of the present invention has an average roundness PA of 0.1 to 0.8, preferably 0.12 to 0.7, more preferably 0.14 to 0.65, and even more preferably 0.16 to 0.6.

[0058] If the average roundness is within the above-mentioned specific range, compared with the conventional adhesive containing water-soluble resin powder, it is difficult to generate agglomerates due to the fusion of resin powder in pipes and silos. The reason for this is not necessarily clear, but it can be inferred that the reason is that the corners of each particle are curved, so the contact area between the particles is small, and as a result, the particles are difficult to fuse.

[0059] The water-soluble resin is not particularly limited as long as it is a resin that has solubility to dissolve more than 1g of the resin relative to 100g of water. For example, as such a water-soluble resin, vinyl alcohol polymers and their derivatives, acrylic polymers such as (meth) acrylic acid and their derivatives, cellulose derivatives such as carboxymethyl cellulose, alginic acid and its neutralizer, polyvinyl pyrrolidone, etc. can be cited.

[0060] Among them, vinyl alcohol polymers and their derivatives have good affinity for active materials used in power storage devices such as carbon materials, metals, and metal oxides, and are therefore suitable for use as water-soluble resins.

[0061] When PVA is used as a water-soluble resin, it is usually regarded as the main component of the water-soluble resin powder. It should be noted that the main component refers to the component with the largest content based on mass. The content of PVA in the non-volatile components of the water-soluble resin powder is preferably 50% by mass or more, more preferably 70% by mass or more, more preferably 90% by mass or more, and sometimes more preferably 99% by mass or more. The upper limit of the content of PVA in the non-volatile components of the water-soluble resin powder can be 100% by mass. As non-volatile components other than PVA that are optionally included in the water-soluble resin powder, additives such as resins, surfactants, plasticizers, defoamers, viscosity modifiers, and various compounds used during manufacture can be cited. In addition, the content of volatile components in the water-soluble resin powder is usually 20% by mass or less, preferably 15% by mass or less, and more preferably 10% by mass or less. As volatile components that can be included in the water-soluble resin powder, alcohol, water, etc. can be cited.

[0062] Vinyl alcohol polymers ("polyvinyl alcohol" or also referred to as "PVA") are polymers having vinyl alcohol units as monomer units (i.e., structural units). PVA is generally obtained by saponifying polyvinyl esters. The proportion of vinyl alcohol units in all monomer units in PVA is preferably 35 mol% or more, more preferably 50 mol% or more, further preferably 70 mol% or more, and sometimes further preferably 80 mol% or more or 90 mol% or more. By setting the proportion of vinyl alcohol units to above the above lower limit, the permeability is improved, especially in an environment with high humidity, and it is easy to efficiently manufacture the water-soluble resin powder in the present invention by a manufacturing method that undergoes crushing and surface processing. On the other hand, the proportion of the above-mentioned vinyl alcohol units can be 100 mol%, preferably 99.99 mol% or less, and more preferably 99 mol% or less.

[0063] The saponification degree of PVA is preferably 35 mol% or more, more preferably 50 mol% or more, further preferably 70 mol% or more, and sometimes further preferably 80 mol% or more or 90 mol% or more. By setting the saponification degree to be above the above lower limit, the adhesion to various components is improved, the battery performance such as discharge capacity is easily improved, and it is easy to efficiently manufacture the water-soluble resin powder in the present invention by a manufacturing method through crushing and surface processing. On the other hand, the above-mentioned saponification degree can be 100 mol% or less, preferably 99.99 mol% or less, and more preferably 99 mol% or less. The saponification degree can be measured by the method described in JIS K6726: 1994.

[0064] PVA may have other monomer units (structural units) in addition to vinyl alcohol units and vinyl ester units. Examples of monomers that provide the above-mentioned other monomer units include α-olefins such as ethylene, propylene, 1-butene, isobutylene, and 1-hexene; acrylic acid, methacrylic acid; acrylic acid esters such as methyl acrylate and ethyl acrylate; methacrylic acid esters such as methyl methacrylate and ethyl methacrylate; acrylamide derivatives such as N-methylacrylamide and N-ethylacrylamide; methacrylamide derivatives such as N-methylmethacrylamide and N-ethylmethacrylamide; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, isopropyl vinyl ether, and n-butyl vinyl ether; hydroxyl-containing vinyl ethers such as ethylene glycol vinyl ether, 1,3-propylene glycol vinyl ether, and 1,4-butanediol vinyl ether; Allyl acetate; allyl ethers such as propyl allyl ether, butyl allyl ether, and hexyl allyl ether; monomers having an oxyalkylene group; isopropenyl acetate; α-olefins containing a hydroxyl group such as 3-butene-1-ol, 4-pentene-1-ol, 5-hexene-1-ol, 7-octen-1-ol, 9-decen-1-ol, and 3-methyl-3-butene-1-ol; monomers having a silyl group such as vinyltrimethoxysilane, vinylmethyldimethoxysilane, vinyldimethylmethoxysilane, vinyltriethoxysilane, vinylmethyldiethoxysilane, vinyldimethylethoxysilane, 3-(meth)acrylamidepropyltrimethoxysilane, and 3-(meth)acrylamidepropyltriethoxysilane, etc. Among these, α-olefins, acrylic acid, methacrylic acid, acrylic acid esters, and methacrylic acid esters are preferred.

[0065] The proportion of the other monomer units in all monomer units in PVA is preferably 20 mol% or less, and more preferably 10 mol% or less. On the other hand, the proportion of the other monomer units may be, for example, 0.1 mol% or more, or 1 mol% or more.

[0066] The viscosity average degree of polymerization of PVA is not particularly limited, but is preferably 200 or more, more preferably 250 or more, further preferably 400 or more, and particularly preferably 600 or more. The above-mentioned viscosity average degree of polymerization is preferably 5,000 or less, more preferably 4,500 or less, and further preferably 3,500 or less. By setting the viscosity average degree of polymerization to the above-mentioned range, the industrial production of resin particles having the above-mentioned average roundness becomes easy. It should be noted that the viscosity average degree of polymerization can be measured in accordance with JIS K6726:1994. That is, PVA is re-saponified to a saponification degree of 99.5 mol% or more, and after purification, the limiting viscosity [η] (unit: liter / g) measured in water at 30°C can be calculated by the following formula.

[0067]

[0068] The average particle size of the water-soluble resin powder (i.e., the particles constituting the water-soluble resin powder) in the present invention is 100 μm or more, preferably 150 μm or more, and more preferably 300 μm or more. By setting the average particle size to be 100 μm or more, dust explosion is less likely to occur, and safety can be improved. The above average particle size is 2,000 μm or less, preferably 1,500 μm or less, more preferably 1,000 μm or less, and further preferably 850 μm or less. By setting the average particle size to be 2,000 μm or less, it is easy to dissolve in a solvent, the occurrence of gel-like agglomerates is suppressed, and a uniform electrode can be produced.

[0069] The average particle size of the water-soluble resin powder (ie, particles constituting the water-soluble resin powder) can be measured according to the method described in JIS K7369:2009.

[0070] It is important that the average roundness (the average PA of the roundness P of 50 particles randomly extracted from particles with a particle size of 100 to 1,000 μm) of the water-soluble resin powder in the present invention (i.e., the particles constituting the water-soluble resin powder) is 0.1 or more, preferably 0.2 or more, more preferably 0.25 or more, further preferably 0.3 or more, particularly preferably 0.33 or more, and sometimes extremely preferably 0.35 or more. By setting the average roundness to 0.1 or more, it is easy to dissolve in a solvent, the occurrence of gel-like agglomerates is suppressed, and a uniform electrode can be produced. On the other hand, it is important that the above average roundness is 0.8 or less, preferably 0.7 or less. By setting the average roundness to 0.8 or less, the productivity of the water-soluble resin powder in the present invention can be improved. In addition, a water-soluble resin powder having an average roundness below the above upper limit can be effectively manufactured by a manufacturing method that performs crushing and surface processing.

[0071] The average roundness of the water-soluble resin powder (i.e., the particles constituting the water-soluble resin powder) can be determined by the following method. Randomly extract 50 particles from the particles with a particle size of 100 to 1,000 μm (or a particle size of 106 to 1,000 μm based on a sieve) in the water-soluble resin powder. In screening, particles with a particle size of 100 to 1,000 μm can be screened as particles that pass through a sieve with a nominal mesh size of 1,000 μm (16 mesh) and do not pass through a sieve with a nominal mesh size of 106 μm (150 mesh). The above-mentioned mechanical screening can be performed by the method described in JIS K7369:2009, for example. For one extracted particle, for the projection diagram with the largest apparent area, the radius of curvature r is used. i Select 8 corners in order from small to large (if the number of corners is less than 8, that is, less than 7, it is all the corners), and measure the curvature radius r of each corner iIn addition, based on the projection diagram with the maximum apparent area, the radius R of the largest inscribed circle of the particle is measured. The number of corners of the particle is denoted as N (when the number of corners of the particle is 9 or more, N is 8), and based on the measured r i The roundness P of one particle is calculated by the following formula (1) using R and R. When the roundness P is low, it means that there are many corners protruding from the particle, and when the roundness P is high, it means that the particle has a curvature.

[0072] [Number 3]

[0073]

[0074] [In formula (1),

[0075] r i is the radius of curvature of each corner of the particle,

[0076] R is the radius of the largest inscribed circle of the particle,

[0077] N is the number of corners a particle has,

[0078] When the number of corners of a particle is 9 or more, the curvature radii of the 8 corners are used in ascending order of curvature radii, and N is set to 8].

[0079] The roundness P of the 50 particles thus sampled is measured, and the average PA of the roundness P of the 50 particles is obtained. The average PA is the average roundness.

[0080] In the water-soluble resin powder of the present invention, the content of particles with a particle size of 100 to 1,000 μm (or a particle size of 106 to 1,000 μm based on a sieve) is not particularly limited, and is preferably 50% by mass or more, more preferably 55% by mass or more, and further preferably 60% by mass or more. On the other hand, the upper limit of the content of particles with a particle size of 100 to 1,000 μm can be 100% by mass. When the content of particles with a particle size of 100 to 1,000 μm is within the above range, it is difficult for particles to fuse with each other in piping and silos, and it is difficult for gel-like agglomerates to occur when the resin powder is dissolved. Concomitantly, when used as an adhesive solution for electrode production, the uniformity (homogeneity) of the electrode is improved. The content of particles having a particle size of 100 to 1,000 μm in the resin powder can be determined according to the method described in JIS K7369:2009 using a sieve with a nominal mesh size of 1,000 μm (16 mesh) and a sieve with a nominal mesh size of 106 μm (150 mesh).

[0081] The water-soluble resin powder in the present invention (i.e., the particles constituting the water-soluble resin powder) preferably satisfies the following formula (2), more preferably satisfies the following formula (2), and has an average particle size of 100 to 1,000 μm. In this case, the fusion of particles and the occurrence of agglomerates, especially under high humidity, can be suppressed. According to the research of the present inventors, there is a tendency that the higher the average roundness, the more difficult it is to cause the fusion of particles. On the other hand, especially under high humidity, the water-soluble resin powder containing PVA with a low degree of saponification is easily fused due to the influence of its hygroscopicity, etc. Therefore, by setting the product (PA×S) of the average value PA (average roundness) of the roundness P and the saponification degree S of PVA to a specified value or more, the fusion of particles can be suppressed even under high humidity.

[0082]

[0083] In formula (2), PA is the average value of the roundness P. S is the saponification degree of PVA (mol %).

[0084] The product (PA×S) of the average PA (average roundness) of the roundness P and the saponification degree S of PVA is more preferably 19 or more, and further preferably 20 or more. On the other hand, the upper limit of the product (PA×S) is not particularly limited, and may be, for example, 80 or less, or 60 or less.

[0085] The angle of repose of the water-soluble resin powder in the present invention measured after humidity adjustment for one week in an atmosphere of 20°C and 30% humidity is preferably less than 38°, more preferably less than 35°. In addition, the angle of repose of the water-soluble resin powder in the present invention measured after humidity adjustment for one week in an atmosphere of 20°C and 65% humidity is preferably less than 40°, more preferably less than 38°. When the angle of repose of the water-soluble resin powder is as low as this, the fusion of particles can be suppressed even in a high humidity environment. It should be noted that the lower limits of these angles of repose are not particularly limited, for example, they can be greater than 25°, or greater than 30°. The angle of repose of the water-soluble resin powder can be controlled to the aforementioned range by controlling the average roundness and the average particle size. In addition, the angle of repose of the water-soluble resin powder can be measured according to the method described in JIS9301-2-2:1999.

[0086] <Method for producing water-soluble resin powder>

[0087] The method for producing the water-soluble resin powder in the present invention is not particularly limited, and the following method is preferably used. That is, in one embodiment of the present invention, the method for producing the water-soluble resin powder includes:

[0088] a step of obtaining a coarse powder of the water-soluble resin by pulverizing a resin solid containing the water-soluble resin (step B); and

[0089] A step of processing the surfaces of particles contained in the coarse powder (step C).

[0090] When PVA is used as the water-soluble resin in the water-soluble resin powder of the present invention, the present invention may further include a step of synthesizing PVA to obtain a resin solid containing PVA (step A).

[0091] (Step A)

[0092] Step A may include, for example, a polymerization step, a saponification step, and the like.

[0093] In the polymerization step, vinyl ester monomers are polymerized to obtain vinyl ester polymers. As methods for polymerizing vinyl ester monomers, for example, known methods such as bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization can be cited. Among these methods, bulk polymerization in the absence of solvents and solution polymerization using solvents such as alcohols are preferred, and solution polymerization in the presence of lower alcohols is more preferred. As the above-mentioned lower alcohol, alcohols with a carbon number of 3 or less are preferred, and methanol, ethanol, n-propanol and isopropanol are more preferred, and methanol is further preferred. When the polymerization reaction is carried out by bulk polymerization or solution polymerization, the reaction method can also be any of intermittent and continuous methods.

[0094] Examples of the vinyl ester monomer include vinyl formate, vinyl acetate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl benzoate, vinyl pivalate, vinyl versatate, etc. Among them, vinyl acetate is preferred.

[0095] As the initiator used in the polymerization reaction, for example, azo initiators such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile); organic peroxide initiators such as benzoyl peroxide and n-propyl peroxycarbonate, and other well-known initiators can be mentioned. There is no particular limitation on the polymerization temperature when performing the polymerization reaction, but a range of 5°C or more and 200°C or less is suitable.

[0096] When the vinyl ester monomer is polymerized, a copolymerizable monomer may be further copolymerized within the scope that does not impair the main purpose of the present invention. When the vinyl ester monomer is polymerized, a chain transfer agent may coexist for the purpose of adjusting the degree of polymerization of the obtained PVA. As the chain transfer agent, aldehydes such as acetaldehyde, propionaldehyde, butyraldehyde, and benzaldehyde; ketones such as acetone, methyl ethyl ketone, hexanone, and cyclohexanone; thiols such as 2-hydroxyethanethiol; thiocarboxylic acids such as thioacetic acid; halogenated hydrocarbons such as trichloroethylene and perchloroethylene, etc., among which aldehydes and ketones are suitable. The amount of chain transfer agent added is determined according to the chain transfer constant of the added chain transfer agent and the degree of polymerization of the target PVA. Generally speaking, it is preferably 0.1~10% by mass relative to the vinyl ester used.

[0097] In the saponification step, the vinyl ester polymer is saponified in an alcohol solution using an alkaline catalyst or an acid catalyst to obtain PVA. In the saponification reaction of the vinyl ester polymer, the alcoholysis or hydrolysis reaction using alkaline catalysts such as sodium hydroxide, potassium hydroxide, sodium methoxide, or acidic catalysts such as p-toluenesulfonic acid, which are known in the past, can be applied. As the solvent used in the saponification reaction, there can be mentioned alcohols such as methanol and ethanol; esters such as methyl acetate and ethyl acetate; ketones such as acetone and methyl ethyl ketone; aromatic hydrocarbons such as benzene and toluene, etc. They can be used alone or in combination of two or more. Among these, it is simple and preferred to use methanol or a mixed solution of methanol and methyl acetate as a solvent and carry out the saponification reaction in the presence of sodium hydroxide as an alkaline catalyst.

[0098] The saponification step can be carried out by a belt reactor, a kneader reactor, a tower reactor, etc. Through the saponification step, a resin solid containing PVA is obtained. The content ratio of PVA in the non-volatile components in the resin solid is, for example, 50% by mass or more, preferably 70% by mass or more, more preferably 90% by mass or more, and sometimes more preferably 99% by mass or more. The non-volatile components in the resin solid can substantially contain PVA as the main component, and can contain impurities such as sodium acetate, by-products, etc.

[0099] (Step B)

[0100] In step B, the resin solids containing water-soluble resins such as PVA are crushed. Thus, a coarse powder containing a water-soluble resin is obtained. The above-mentioned crushing can be carried out by a known crusher. As a crusher, in order to adjust the average particle size of the obtained coarse powder and the particles constituting the final resin powder, it is preferably a device that can control the degree of crushing such as crushing strength. In addition to the adjustment of the crushing strength, the average particle size of the particles constituting the obtained coarse powder can be controlled by the processing time, etc. The average particle size of the particles constituting the coarse powder is not limited. In the case of surface processing in step C described later, considering the reduction of particle size caused by this step, it is preferably set to be greater than or equal to the average particle size of the final resin powder. For example, by setting the average particle size of the particles constituting the coarse powder to 100~3000μm, a resin powder with a desired average particle size is finally obtained. It should be noted that the obtained coarse powder can be subjected to a saponification treatment again. In addition, the obtained coarse powder can be subjected to a washing treatment for reducing impurities such as sodium acetate, by-products, etc., and a drying treatment for reducing volatile components, etc. The resin solids before pulverization may be subjected to washing treatment and drying treatment.

[0101] (Step C)

[0102] In step C, the surface of the particles constituting the coarse powder is processed. When a resin solid containing a water-soluble resin such as PVA is crushed, the resulting coarse powder generally has a shape with very sharp corners. Therefore, by rounding the corners in step C, a water-soluble powder having an average roundness within a specified range can be efficiently obtained.

[0103] As the device used in step C, there is no particular limitation as long as it can grind the surface of the coarse powder. For example, a rotary kiln in which the powder filling container rotates and the powders contact each other, thereby performing surface grinding; a planetary motion mixer that can give three-dimensional motion to the contents by rotating and revolving screw blades in the container; a mixer in which the paddles and screws in the container rotate, and the internal powder is ground by its rotation. As a mixer, a high-speed mixer, a Henschel mixer, a turbulence enhancer, a Lodige mixer, etc. can be cited. Among these, from the viewpoint of processing efficiency, a mixer is preferred, and a turbulence enhancer and a Lodige mixer are more preferred. In addition, in step C, the surface processing of the coarse powder can be performed while heating.

[0104] The method for producing a water-soluble resin powder in the present invention may further include a sieving step for adjusting the average particle size, etc. After step C, washing treatment or drying treatment may be performed.

[0105] <Binder solution for storage device electrodes>

[0106] The adhesive of the present invention may further contain a material for adjusting the viscosity of the adhesive in a solution state. As the material for adjusting the viscosity, inorganic substances such as polyacids such as citric acid, tartaric acid, aspartic acid and their salts, their condensates, pyrogenic silica, and alumina can be cited. Their addition amount is not particularly limited, and is usually preferably 0.01 mass parts or more and 10 mass parts or less, more preferably 0.02 mass parts or more and 8 mass parts or less, and further preferably 0.05 mass parts or more and 5 mass parts or less relative to 100 mass parts of PVA. The more the material for adjusting the viscosity contains, the more the viscosity of the adhesive of the present invention in a solution state can be increased. The smaller the particle size of the inorganic substance, the easier it is to increase the viscosity of the adhesive in a solution state.

[0107] The adhesive of the present invention or the adhesive solution for the storage device electrode of the present invention described later may further contain a compounding agent within the scope of the effect of the present invention without damaging it. As a compounding agent, for example, a light stabilizer, an ultraviolet absorber, a freezing stabilizer, a thickener, a leveling agent, a rheological stabilizer, a thixotropic agent, a defoamer, a plasticizer, a lubricant, a preservative, a rust inhibitor, an antistatic agent, an antistatic agent, an anti-yellowing agent, a pH adjuster, a film-forming aid, a curing catalyst, a cross-linking reaction catalyst, a cross-linking agent (glyoxal, urea resin, melamine resin, polyvalent metal salt, polyisocyanate, polyamide epichlorohydrin, etc.), a dispersant, etc. can be cited. It can be selected or combined according to the respective purposes. The content of the compounding agent is based on the total amount of the adhesive or the adhesive solution for the storage device electrode, for example, 10% by mass or less, preferably 5% by mass or less, and more preferably 1% by mass or less.

[0108] The adhesive of the present invention can be obtained by dissolving a water-soluble resin, particularly PVA, and components other than the water-soluble resin as required in a solvent (e.g., water or NMP) to form a solution, removing the solvent. In addition, the solution can also be directly used as an adhesive solution for storage device electrodes of the present invention described later for the preparation of subsequent slurry. In this case, the composition of the components other than the solvent in the adhesive solution is the adhesive of the present invention. The adhesive of the present invention is included in the cured body of the slurry composition of the present invention in a state mixed with components such as active materials.

[0109] The adhesive solution as one embodiment of the present invention comprises an adhesive of the present invention and at least one solvent. The solvent is preferably water or NMP. When the solvent is water, it is suitable from the viewpoint of reducing environmental burden and simplicity of equipment. On the other hand, when the solvent is NMP, especially when used as a positive electrode slurry, the active material in the slurry is not degraded, so it is suitable.

[0110] In addition to the aforementioned adhesive of the present invention, the adhesive solution may contain an additive (referred to as additive A) that can be dissolved in a solvent, within the scope of not impairing the effects of the present invention. Examples of additive A include polyethylene glycol, polyethylene glycol dimethyl ether, polyethylene glycol diglycidyl ether, polyethyleneimine, and the like. The content of additive A is, for example, 10% by mass or less, preferably 5% by mass or less, and more preferably 1% by mass or less, based on the total amount of the adhesive solution. In particular, it is preferred that additive A is not contained.

[0111] The adhesive solution is obtained by mixing a water-soluble resin such as PVA, a solvent (such as water or NMP), and the aforementioned components other than the aqueous solution resin as required by a known method, such as stirring. The mixing temperature and mixing time can be appropriately adjusted according to the type of solvent. It should be noted that the adhesive solution represents a solution in which the aforementioned water-soluble resin is dissolved in a solvent. The dissolved state refers to a water-soluble resin completely dissolved in a solvent, especially a mass of PVA relative to the total mass (100 mass %) of the water-soluble resin used when making the adhesive solution, preferably 80 mass % or more, more preferably 90 mass % or more, further preferably 95 mass % or more, further preferably 99 mass % or more, and further preferably 100 mass % state.

[0112] The content of the water-soluble resin, especially PVA, in the adhesive solution of the present invention is preferably 1% by mass or more and 30% by mass or less, more preferably 3% by mass or more and 20% by mass or less, and particularly preferably 5% by mass or more and 15% by mass or less based on the total amount of the adhesive solution. If the content of the water-soluble resin is 1% by mass or more, it is easy to improve the adhesion of the active material on the current collector when forming an electrode. If the content of the water-soluble resin is 30% by mass or less, it is possible to suppress the rapid aggregation of the active material when forming an electrode.

[0113] <Electrode slurry for power storage devices>

[0114] The electrical storage device electrode slurry according to one embodiment of the present invention contains the above-mentioned binder solution and an active material.

[0115] The slurry can be used for either the positive electrode or the negative electrode. In addition, it can also be used for both the positive electrode and the negative electrode. The active material can be either the positive electrode active material or the negative electrode active material. In addition, the type of solvent is not particularly limited, and water or NMP solvent can be preferably used, and two or more solvents can be used alone or in combination.

[0116] As the negative electrode active material, for example, a material that has been used as a negative electrode active material for power storage devices can be used. Examples thereof include amorphous carbon, artificial graphite, natural graphite (graphite), mesocarbon microbeads (MCMB), pitch-based carbon fibers, carbon black, activated carbon, carbon fibers, hard carbon, soft carbon, mesoporous carbon, and carbonaceous materials such as conductive polymers such as polyacene, Si, SiO x Silicon compounds, SnO x and LiTiO x The composite metal oxides shown, other metal oxides, lithium metals, lithium alloys and other lithium-based metals, TiS 2 and LiTiS 2 Metal compounds such as , composite materials of metal oxides and carbonaceous materials, hydrogen absorbing alloys, etc. These negative electrode active materials can be used alone or in combination of two or more.

[0117] As the positive electrode active material, for example, a material that has been used as a positive electrode active material for power storage devices can be used. As an example, TiS 2 、TiS 3 , amorphous MoS 3 , Cu 2 V 2 O 3 、Amorphous V 2 OP 2 O 5 、MoO 3 、V 2 O 5 and V 6 O 13 Transition metal oxides, and LiCoO 2 、LiNiO 2 、LiMnO 2 、LiMn 2 O 4 The positive electrode active materials include lithium composite metal oxides, manganese dioxide, nickel hydroxide, nickel oxyhydroxide, etc. These positive electrode active materials may be used alone or in combination of two or more.

[0118] The slurry may contain a conductive aid. The conductive aid is used to increase the output power of the power storage device and can be appropriately selected according to the situation of being used for the positive electrode or the negative electrode. As examples thereof, graphite, acetylene black, carbon black, Ketjen black, vapor-grown carbon fiber, etc. can be cited. From the viewpoint of easily increasing the output power of the obtained power storage device, acetylene black is preferably used among these.

[0119] When the slurry contains a conductive auxiliary agent, the content of the conductive auxiliary agent is preferably 0.1 parts by mass or more and 15 parts by mass or less, more preferably 1 part by mass or more and 10 parts by mass or less, and further preferably 3 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the active material. If the content of the conductive auxiliary agent is within this range, the capacity of the battery to which the slurry is applied is not reduced, and a sufficient conductive auxiliary effect can be obtained.

[0120] Preferably, the content of the adhesive in the slurry is 0.1 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the active material. If the content is 0.1 parts by mass or more, the adhesion of the active material on the current collector is improved, which is beneficial from the perspective of maintaining the durability of the applied battery. Further, if the content is 20 parts by mass or less, the discharge capacity is easily improved. The range of the content is more preferably 0.2 parts by mass or more and 18 parts by mass or less, more preferably 0.5 parts by mass or more and 16 parts by mass or less, and more preferably 1 part by mass or more and 12 parts by mass or less.

[0121] In addition to the binder, active material, conductive additive and solvent, the slurry may contain additives such as flame retardant, thickener, defoamer, leveling agent, adhesion imparting agent, etc. as needed. When these additives are included, the content of the additives is preferably 0.1% by mass or more and 10% by mass or less based on the total amount of the slurry.

[0122] The slurry can be obtained by mixing the binder, the active material, and, if necessary, the conductive additive, the solvent, and additives by a conventional method, for example, using a mixer such as a ball mill, a blending mill, or a three-roll mill.

[0123] <Electrodes for power storage devices>

[0124] The electrical storage device electrode as one embodiment of the present invention includes the solidified body of the slurry described above and a current collector. The solidified body of the slurry is a solidified product obtained by removing the solvent in the slurry by drying or the like.

[0125] The electrode can be obtained by applying the slurry of the present invention onto a current collector and removing the solvent by drying etc. In addition, the electrode can be subjected to a rolling treatment after drying.

[0126] The current collector is not particularly limited as long as it contains a conductive material. Examples include metal materials such as iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, platinum, etc. These current collectors can be used alone or in combination of two or more. Among the current collectors, from the viewpoint of the adhesion of the active material and the discharge capacity, copper is preferably used as the negative electrode current collector, and aluminum is preferably used as the positive electrode current collector.

[0127] The method for coating the slurry on the current collector is not particularly limited, and examples thereof include extrusion coater, reverse roll, knife coater, applicator, etc. The amount of the slurry to be coated is appropriately selected depending on the desired thickness of the cured product derived from the slurry composition.

[0128] Examples of the rolling method for the electrode include methods using a die press, a roll press, etc. The pressing pressure is preferably 1 MPa or more and 40 MPa or less from the viewpoint of easily increasing the battery capacity.

[0129] In the electrode of the present invention, the thickness of the current collector is preferably 1 μm or more and 200 μm or less, more preferably 2 μm or more and 150 μm or less. The thickness of the solid body is preferably 10 μm or more and 800 μm, more preferably 20 μm or more and 600 μm or less. The thickness of the electrode is preferably 20 μm or more and 300 μm or less.

[0130] <Electrical storage equipment>

[0131] An electric storage device according to one embodiment of the present invention includes the above-described electric storage device electrode as a negative electrode and / or a positive electrode.

[0132] Examples of the power storage device include lithium ion secondary batteries, sodium ion batteries, lithium sulfur batteries, all-solid batteries, lithium ion capacitors, lithium batteries, nickel hydrogen batteries, and alkaline dry batteries.

[0133] The electrode of the electric storage device of the present invention has excellent uniformity, low resistance and high discharge capacity.

[0134] In addition, the discharge capacity of the electric storage device can be calculated by a method of performing a charge and discharge test using a commercially available charge and discharge tester, for example, as described in the examples below.

[0135] The electrolyte contained in the power storage device is a solution in which an electrolyte is dissolved in a solvent. As long as the electrolyte is used in a common battery, it can be in a liquid or gel state, and a substance that functions as a battery can be appropriately selected according to the types of negative electrode active material and positive electrode active material. As a specific electrolyte, for example, in a non-aqueous electrolyte battery, a well-known lithium salt can be suitably used, and LiClO 4 , LiBF 6 、LiPF 6 、LiCF 3 SO 3 、LiCF 3 CO 2 、LiAsF 6 、LiSbF 6 , LiB 10 Cl 10 、LiAlCl 4、LiCl、LiBr、LiB(C 2 H 5 ) 4 CF 3 SO 3 Li, CH 3 SO 3 Li、LiCF 3 SO 3 ,LiC 4 F 9 SO 3 、Li(CF 3 SO 2 ) 2 N, lithium lower aliphatic carboxylate, etc. In the battery using an aqueous electrolyte, for example, an alkaline aqueous solution containing potassium hydroxide, sodium hydroxide, or lithium hydroxide as a solute can be mentioned.

[0136] The solvent contained in the electrolyte is not particularly limited. Specific examples thereof include carbonates such as propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and vinylene carbonate, lactones such as γ-butyrolactone, ethers such as trimethoxymethane, 1,2-dimethoxyethane, diethyl ether, 2-ethoxyethane, tetrahydrofuran, and 2-methyltetrahydrofuran, sulfoxides such as dimethyl sulfoxide, and oxolanes such as 1,3-dioxolane and 4-methyl-1,3-dioxolane. Cyclopentane, acetonitrile, nitromethane and other nitrogen-containing compounds, methyl formate, methyl acetate, ethyl acetate, butyl acetate, methyl propionate and ethyl propionate and other organic acid esters, triethyl phosphate, dimethyl carbonate and diethyl carbonate and other inorganic acid esters, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, cyclopentane, 3-methyl-2-oxazolidinone and other oxazolidinone, 1,3-propane sultone, and 1,4-butane sultone and naphthoic acid sultone and other sultones, water, etc. They can be used alone or in combination of two or more. When using a gel electrolyte, as a gelling agent, a nitrile polymer, an acrylic polymer, a fluorine polymer, an oxyalkylene polymer, etc. can be added.

[0137] When the electrode of the present invention is used for either the positive electrode or the negative electrode, a conventional electrode may be used for the electrode not using the electrode of the present invention.

[0138] In one preferred embodiment, the electrical storage device of the present invention includes the electrode of the present invention as a negative electrode and a conventional electrode as a positive electrode. The positive electrode is not particularly limited as long as it is a positive electrode commonly used in electrical storage devices.

[0139] Alternatively, in another preferred embodiment, the electrical storage device of the present invention includes the electrode of the present invention as a positive electrode and a conventional electrode as a negative electrode. The negative electrode is not particularly limited as long as it is a negative electrode commonly used in electrical storage devices.

[0140] Furthermore, both the positive electrode and the negative electrode may be electrodes containing the binder of the present invention.

[0141] The method for manufacturing the power storage device of the present invention is not particularly limited, and can be manufactured as follows, for example. That is, the negative electrode and the positive electrode are overlapped with a separator such as a polypropylene porous film, and the battery is rolled and / or folded according to the shape of the battery, added to the battery container, and the electrolyte is injected and sealed. The shape of the battery can be a known coin type, button type, sheet type, cylindrical type, square type, flat type, etc.

[0142] The power storage device of the present invention is useful in various applications. For example, it is very useful as a battery used in a portable terminal that requires miniaturization, thinning, lightness, and high performance. In addition, it is also applicable to batteries for devices that require flexibility, such as wound dry batteries and laminated batteries. Example

[0143] The present invention is specifically described by the following examples, but the present invention is not limited by these examples. The physical properties of each PVA used in each of the following examples and comparative examples, the evaluation of the adhesive aqueous solution and NMP solution containing the PVA, the evaluation in electrode application, and the evaluation in battery application were measured according to the following methods.

[0144] [Viscosity average degree of polymerization of PVA]

[0145] The viscosity average polymerization degree of PVA is measured in accordance with JIS K6726: 1994. Specifically, when the saponification degree of PVA is less than 99.5 mol %, the PVA is saponified to a saponification degree of 99.5 mol % or more, and the viscosity average polymerization degree is calculated by the following formula using the limiting viscosity [η] (liter / g) measured in water at 30°C for the obtained PVA.

[0146]

[0147] [Saponification degree of PVA]

[0148] The saponification degree of PVA (including modified PVA) is determined by the method described in JIS K6726:1994.

[0149] [Average particle size of particles constituting the (water-soluble) resin powder, and content of particles with a particle size of 100 to 1,000 μm]

[0150] The average particle size of the resin powder and the content of particles having a particle size of 100 to 1,000 μm (or a particle size of 106 to 1,000 μm based on the sieve) were determined by the method described in JIS K7369:2009 using a JIS standard sieve.

[0151] [Average roundness of (water-soluble) resin powder]

[0152] Particles with a particle size of 100 to 1,000 μm (or a particle size of 106 to 1,000 μm based on a sieve) are selected by the above sieving, and 50 particles are randomly selected from these particles. The curvature radius r is calculated based on an image of these particles at a magnification of 100 times using a digital microscope VHX-900 manufactured by Keyence Co., Ltd. i The roundness P of each particle is calculated by the radius R of the largest inscribed circle. The average PA of the roundness P of 50 particles is calculated as the average roundness.

[0153] [Angle of repose of (water-soluble) resin powder]

[0154] The resin powder was humidified in an atmosphere of 20°C and 30% humidity or 20°C and 65% humidity for 1 week. Thereafter, the angle of repose of the resin powder was measured using a multifunctional tester MT-1001 manufactured by Seishin Enterprise Co., Ltd. The angle of repose was measured according to the method described in JIS 9301-2-2: 1999. It should be noted that the inventors have confirmed that the smaller the angle of repose of the resin powder, the less likely it is for particles to fuse and form agglomerates in pipes and silos.

[0155] [Evaluation of Solubility of (Water-Soluble) Resin Powder]

[0156] In order to confirm the solubility of the resin powder in the solvent (water or NMP), add water or NMP 95 parts by mass to 5 parts by mass of PVA, raise the temperature to 95°C while stirring, heat and stir for 4 hours, and visually observe the dissolution of PVA. After cooling, the solubility is evaluated according to the following criteria through a metal mesh with a mesh size of 3 mm. For the resin powder evaluated as A, when used as an adhesive, the uniformity of the electrode can be improved.

[0157] A: No residue was found on the metal mesh.

[0158] B: Transparent gel-like lumps were observed on the metal mesh.

[0159] C: Opaque gel-like lumps were observed on the metal mesh.

[0160] [Evaluation of electrode uniformity (homogeneity) in negative and positive electrode applications]

[0161] In order to evaluate the uniformity (homogeneity) of the negative electrode and the positive electrode prepared in each of the examples and comparative examples described below, the film thickness deviation of the coated electrode for the battery was used as an index, and 4 electrodes were measured at 3 points each. According to the following criteria, the judgment was made as ◎, ○, △, and ×. The discharge capacity and DC resistance evaluated as ◎ and ○ were excellent, and those evaluated as ◎ were particularly excellent.

[0162] ◎: Deviation from the average film thickness is less than 1 μm

[0163] ○: Deviation from the average film thickness is greater than 1 μm and less than 2 μm

[0164] △: Deviation from the average film thickness is greater than 2 μm and less than 3 μm

[0165] ×: Deviation from the average film thickness is greater than 3 μm

[0166] [Discharge capacity and DC resistance of lithium-ion secondary batteries in negative electrode applications]

[0167] The coin cells produced in the following examples and comparative examples were tested using a commercially available charge and discharge tester (TOSCAT3100, manufactured by Toyo System). After the initial charge, the resistance value when a current of 0.1 mA was passed for 3 seconds was taken as the DC resistance. During the charge, a 0.2C (approximately 1 mA / cm 2 ) constant current to 0.01 V, and then further charged at a constant voltage of 0.01 V relative to the lithium potential until a current of 0.02 mA was reached. During discharge, 0.2 C (about 0.5 mA / cm 2 ) was discharged at a constant current until it reached 1.5 V. The coin battery was placed in a constant temperature chamber at 25° C., and initial charge and discharge were performed under the above conditions, and the discharge capacity and DC resistance were measured.

[0168] [Discharge capacity and DC resistance of lithium-ion secondary batteries in positive electrode applications]

[0169] The coin cells produced in the following examples and comparative examples were tested using a commercially available charge and discharge tester (TOSCAT3100, manufactured by Toyo System). After the initial charge, the resistance value when a current of 0.1 mA was passed for 3 seconds was recorded as the DC resistance. During the charge, a 0.2 C (about 1 mA / cm 2 ) to 4.2 V. During discharge, 0.2 C (about 0.5 mA / cm 2 ) was discharged at a constant current of 3 V. The coin battery was placed in a constant temperature chamber at 25° C., and initial charge and discharge were performed under the above conditions, and the discharge capacity and DC resistance were measured.

[0170] [Discharge capacity and DC resistance of manganese dioxide lithium batteries in positive electrode applications]

[0171] The coin cells produced in the following embodiments and comparative examples were tested using a commercially available charge and discharge tester (TOSCAT3100, manufactured by Toyo System). The resistance value when a current of 0.1 mA was passed for 3 seconds before discharge was taken as the DC resistance value. A preliminary discharge was performed until the battery voltage reached 3.2 V, followed by a constant resistance discharge (15 kΩ), and the discharge capacity was measured until 2.0 V.

[0172] [Discharge capacity and DC resistance of NiMH batteries in positive and negative electrode applications]

[0173] The coin batteries produced in the following embodiments and comparative examples were tested using a commercially available charge and discharge tester (TOSCAT3100, manufactured by Toyo System). The coin battery was placed in a constant temperature chamber at 25°C, charged at 0.2C, and then discharged at 0.4C until the battery voltage reached 1.0V. The above charge and discharge operation was repeated 5 times for initial activation. The resistance value when a current of 0.1mA flows for 3 seconds after the initial activation is taken as the DC resistance value. The coin battery after initial activation is charged at 0.1C, and discharged at 0.2C until the battery voltage reaches 1.0V. The capacity at this time is measured as the discharge capacity.

[0174] ・Preparation of negative electrode slurry for lithium-ion secondary batteries

[0175] The above-mentioned adhesive aqueous solution with a solid content concentration of 5% by mass, artificial graphite (FSN-1, manufactured by China Shanshan) as the negative electrode active material, and Super-P (manufactured by Timcal) as the conductive additive (conductive imparting agent) are placed in a dedicated container and kneaded using a planetary mixer (ARE-250, manufactured by Thinky Co., Ltd.) to prepare the negative electrode slurry. When added, the solid content in the adhesive aqueous solution reaches 3 parts by mass, the solid content of artificial graphite reaches 96 parts by mass, and the solid content of Super-P reaches 1 part by mass. That is, the composition ratio of the active material, conductive additive and adhesive in the negative electrode slurry is based on the solid content, graphite powder: conductive additive: adhesive = 96:1:3 (mass ratio).

[0176] ・Manufacturing of negative electrodes for lithium-ion secondary batteries

[0177] The negative electrode slurry obtained as described above was applied to a current collector of copper foil (CST8G, manufactured by Fukuda Metal Foil Powder Industry Co., Ltd.) using a rod coater (T101, manufactured by Matsuo Industry Co., Ltd.). After drying once at 80°C for 30 minutes using a hot air dryer, it was rolled using a roller press (manufactured by Hohsen Co., Ltd.). Thereafter, the battery electrodes ( 14 mm), and then dried at 140°C for 3 hours and then under reduced pressure to produce a negative electrode for a coin cell. The uniformity of the electrode for the produced negative electrode for a coin cell was evaluated by the above method. The results are summarized in Table 3 below.

[0178] ・Manufacturing of lithium-ion secondary batteries

[0179] The negative electrode for the battery obtained as described above was transferred to a glove box (manufactured by Miwa Seisakusho Co., Ltd.) under an argon atmosphere. A metal lithium foil (thickness 0.2 mm, 16mm), the separator used was polypropylene (CELGARD#2400, manufactured by Polypore), and the electrolyte used was lithium hexafluorophosphate (LiPF 6 ), a mixed solvent system (1M-LiPF 6 、EC / EMC=3 / 7vol%VC 2 % by mass, and injected. With the above-mentioned structure, a coin cell (2032 type) was manufactured. The discharge capacity and DC resistance value of the manufactured coin cell were measured by the above-mentioned method. The results are summarized in Table 3 described below.

[0180] ・Preparation of slurry for positive electrode of lithium-ion secondary battery

[0181] Furthermore, the aforementioned binder NMP solution with a solid content concentration of about 5% by mass, NCM (manufactured by Nippon Chemical Industry Co., Ltd., "CellSeed C-5H") as a positive electrode active material, and Super-P (manufactured by Timcal Co., Ltd.) as a conductive aid (conductive imparting agent) are put into a special container and kneaded using a planetary agitator (ARE-250, manufactured by Thinky Co., Ltd.) to prepare a positive electrode slurry. When put in, the solid content in the binder NMP solution reaches 3 parts by mass, NCM reaches 95 parts by mass, and the solid content of Super-P reaches 2 parts by mass. That is, the composition ratio of the active material, conductive aid and binder in the positive electrode slurry is based on the solid content, NCM powder: conductive aid: binder = 95:2:3 (mass ratio).

[0182] ・Manufacturing of positive electrodes for lithium-ion secondary batteries

[0183] The positive electrode slurry obtained as described above was coated on a current collector of aluminum foil (CST8G, manufactured by Fukuda Metal Foil Powder Industry Co., Ltd.) using a rod coater (T101, manufactured by Matsuo Industry Co., Ltd.). After drying once at 80°C for 30 minutes using a hot air dryer, it was rolled using a roller press (manufactured by Hohsen Co., Ltd.). Thereafter, it was punched into battery electrodes ( 14 mm), and then dried at 140°C for 3 hours and then under reduced pressure to produce a positive electrode for a coin cell. The uniformity of the electrode was evaluated for the produced positive electrode for a coin cell by the above method. The results are summarized in Table 3 below.

[0184] ・Manufacturing of lithium-ion secondary batteries

[0185] The positive electrode for the battery obtained as described above was transferred to a glove box (manufactured by Miwa Seisakusho Co., Ltd.) under an argon atmosphere. A metal lithium foil (thickness 0.2 mm, 16mm), the separator used was polypropylene (CELGARD#2400, manufactured by Polypore), and the electrolyte used was lithium hexafluorophosphate (LiPF 6 ), a mixed solvent system (1M-LiPF 6 、EC / EMC=3 / 7vol%VC 2 % by mass, and injected. With the above-mentioned structure, a coin cell (2032 type) was manufactured. The discharge capacity and DC resistance value of the manufactured coin cell were measured by the above-mentioned method. The results are summarized in Table 3 described below.

[0186] ・Preparation of slurry for positive electrode of manganese dioxide lithium battery

[0187] The above-mentioned adhesive aqueous solution with a solid content concentration of 5% by mass, manganese dioxide as a positive electrode active material, and Super-P (manufactured by Timcal Co., Ltd.) as a conductive aid (conductive imparting agent) are placed in a special container and kneaded using a planetary mixer (ARE-250, manufactured by Thinky Co., Ltd.) to prepare a positive electrode slurry. When put in, the solid content in the adhesive aqueous solution reaches 3 parts by mass, the solid content of manganese dioxide reaches 95 parts by mass, and the solid content of Super-P reaches 2 parts by mass. That is, the composition ratio of the active material, conductive aid and adhesive in the positive electrode slurry is based on the solid content, manganese dioxide powder: conductive aid: adhesive = 95:2:3 (mass ratio). It should be noted that the obtained slurry is not limited to manganese dioxide lithium batteries, but can also be used for alkaline dry batteries, etc.

[0188] ・Manufacturing of positive electrode for manganese dioxide lithium battery

[0189] The positive electrode slurry obtained as described above was coated on a current collector of aluminum foil (CST8G, manufactured by Fukuda Metal Foil Powder Industry Co., Ltd.) using a rod coater (T101, manufactured by Matsuo Industry Co., Ltd.). After drying once at 80°C for 30 minutes using a hot air dryer, it was rolled using a roller press (manufactured by Hohsen Co., Ltd.). Thereafter, it was punched into battery electrodes ( 14mm), and then dried at 140°C for 3 hours, and then dried under reduced pressure to produce a positive electrode for a coin battery. The uniformity of the electrode was evaluated by the above method for the produced positive electrode for a coin battery. The results are summarized in Table 3 described below. It should be noted that the obtained electrode is not limited to manganese dioxide lithium batteries, but can also be used for alkaline dry batteries, etc.

[0190] ・Manufacturing of manganese dioxide lithium battery

[0191] The positive electrode for the battery obtained as described above was transferred to a glove box (manufactured by Miwa Seisakusho Co., Ltd.) under an argon atmosphere. A metal lithium foil (thickness 0.2 mm, 16mm), the separator used was polypropylene (CELGARD#2400, manufactured by Polypore), and the electrolyte used was lithium hexafluorophosphate (LiPF 6 ), a mixed solvent system (1M-LiPF 6 、EC / EMC=3 / 7vol%VC 2 % by mass, and injected. With the above-mentioned structure, a coin cell (2032 type) was manufactured. The discharge capacity and DC resistance value of the manufactured coin cell were measured by the above-mentioned method. The results are summarized in Table 3 described below.

[0192] ・Preparation of slurry for negative electrode of nickel-metal hydride battery

[0193] The above-mentioned adhesive aqueous solution with a solid content concentration of 5% by mass, the hydrogen absorbing alloy as the negative electrode active material, and Super-P (manufactured by Timcal Co., Ltd.) as the conductive auxiliary agent (conductive imparting agent) are placed in a dedicated container and kneaded using a planetary mixer (ARE-250, manufactured by Thinky Co., Ltd.) to prepare the negative electrode slurry. When added, the solid content in the adhesive aqueous solution reaches 3 parts by mass, the solid content of the hydrogen absorbing alloy reaches 95 parts by mass, and the solid content of Super-P reaches 2 parts by mass. That is, the composition ratio of the active material, the conductive auxiliary agent and the adhesive in the negative electrode slurry is calculated on a solid basis, and the hydrogen absorbing alloy: conductive auxiliary agent: adhesive = 95:2:3 (mass ratio).

[0194] ・Manufacturing of negative electrodes for nickel-metal hydride batteries

[0195] The negative electrode slurry obtained as described above was applied to a current collector of an iron punching metal (thickness 60 μm, pore size 1.2 mm, porosity 40%) with nickel plating on the surface using a rod coater (T101, manufactured by Matsuo Sangyo Co., Ltd.). After drying once with a hot air dryer at 80°C for 30 minutes, it was rolled using a roller press (manufactured by Hohsen Co., Ltd.). Thereafter, the battery electrode ( 14 mm), and then dried at 140°C for 3 hours and then under reduced pressure to produce a negative electrode for a coin cell. The uniformity of the electrode for the produced negative electrode for a coin cell was evaluated by the above method. The results are summarized in Table 3 below.

[0196] ・Preparation of slurry for positive electrode of nickel-metal hydride battery

[0197] The above-mentioned adhesive aqueous solution with a solid content concentration of 5% by mass, nickel hydroxide as a positive electrode active material, and Super-P (manufactured by Timcal Co., Ltd.) as a conductive aid (conductive imparting agent) are placed in a dedicated container and kneaded using a planetary mixer (ARE-250, manufactured by Thinky Co., Ltd.) to prepare a positive electrode slurry. When added, the solid content in the adhesive aqueous solution reaches 3 parts by mass, the solid content of nickel hydroxide reaches 95 parts by mass, and the solid content of Super-P reaches 2 parts by mass. That is, the composition ratio of the active material, conductive aid and adhesive in the positive electrode slurry is based on the solid content, nickel hydroxide: conductive aid: adhesive = 95:2:3 (mass ratio).

[0198] ・Manufacturing of positive electrodes for nickel-metal hydride batteries

[0199] The positive electrode slurry obtained as described above was applied to a nickel foam (surface density (weight per unit area) of about 300 g / m) using a bar coater (T101, manufactured by Matsuo Sangyo Co., Ltd.). 2 , thickness of about 1.0 mm) on a current collector. After drying once at 80°C for 30 minutes with a hot air dryer, it was rolled using a roller press (manufactured by Hohsen Co., Ltd.). Thereafter, it was punched into battery electrodes ( 14 mm), and then dried at 140°C for 3 hours and then under reduced pressure to produce a positive electrode for a coin cell. The uniformity of the electrode was evaluated for the produced positive electrode for a coin cell by the above method. The results are summarized in Table 3 below.

[0200] ・Manufacturing of nickel-metal hydride batteries

[0201] A coin cell was prepared using the negative electrode and positive electrode for nickel-hydrogen battery obtained as described above. A polypropylene-based (CELGARD#2400, manufactured by Polypore) separator was used, and an alkaline electrolyte containing NaOH was injected as the electrolyte. An aqueous solution containing 7.5 mol / L NaOH was used as the alkaline electrolyte. A coin cell (2032 type) was prepared using the above-described structure. The discharge capacity and DC resistance value of the prepared coin cell were measured by the above-described method. The results are summarized in Table 3 described below.

[0202] [Example 1] Production of PVA1 resin powder 1

[0203] Into a 250L reactor equipped with a stirrer, a reflux condenser, a nitrogen inlet pipe, and an initiator addition port, 112.5kg of vinyl acetate and 37.5kg of methanol (75% by mass of vinyl acetate: 25% by mass of methanol) were added, nitrogen bubbling was performed, and nitrogen substitution in the system was performed for 30 minutes. The temperature of the reactor was started, and when the internal temperature reached 60°C, 35g of 2,2'-azobisisobutyronitrile (AIBN) was added to start polymerization. When the polymerization rate reached 50%, the polymerization was stopped by cooling. The solid content concentration at the time of polymerization stopping was 37.0%. Then, methanol was continuously added at 30°C and under reduced pressure, and unreacted vinyl acetate monomer was removed at the same time to obtain a methanol solution of polyvinyl acetate (PVAc) (concentration 35%). Furthermore, 1.86 kg of an alkali solution (10% methanol solution of sodium hydroxide) was added to 54.05 kg of a methanol solution of PVAc (20 kg of PVAc in the solution) prepared by adding methanol, and saponification was performed (PVAc concentration of the saponified solution was 30%, and the molar ratio of sodium hydroxide to the vinyl acetate unit in PVAc was 0.02 mol%). After the addition of the alkali solution, a gel-like substance (resin solid) was generated in about 1 minute, so it was crushed with a grinder (mixer) for 5 minutes. The crushed substance was placed at 40°C for 1 hour, and after saponification, 50 kg of methyl acetate was added to neutralize the remaining alkali. Using a phenolphthalein indicator, after confirming that the neutralization was completed, a white solid was filtered out, 200 kg of methanol was added thereto, and it was placed at room temperature for washing for 3 hours. After repeating the above-mentioned washing operation 3 times, the white solid obtained by centrifugal dehydration was placed in a dryer at 65°C for 2 days to obtain a coarse powder of PVA1. The degree of polymerization of PVA1 was 1,700, and the degree of saponification was 98.5 mol %.

[0204] Next, the coarse powder of PVA1 was filled in a Rocky mixer "FKM130D" equipped with a Becker-type shovel manufactured by Chuo Machinery Co., Ltd., and surface processing was performed at a rotation speed of 160 rpm for 3 hours at room temperature in a nitrogen atmosphere. Thus, a resin powder 1 having an average particle size of 650 μm and an average roundness of 0.25 was obtained.

[0205] [Examples 2-10, 15-16]

[0206] Except for setting the conditions shown in Table 1, the same method as in Example 1 was carried out to obtain resin powder 2 of PVA2 and the like.

[0207] [Example 11]

[0208] Into a 250L reactor having a stirrer, a reflux condenser, a nitrogen inlet, a comonomer addition port and an initiator addition port, 120.0kg of vinyl acetate and 30.0kg of methanol (80% by mass of vinyl acetate: 20% by mass of methanol) were added, and nitrogen bubbling was performed while nitrogen substitution in the system was performed for 30 minutes. The temperature of the reactor was started to rise, and when the internal temperature reached 60°C, 2.5kg of acetaldehyde and 35g of 2,2'-azobisisobutyronitrile (AIBN) were added to start polymerization. When the polymerization rate reached 50%, the polymerization was stopped by cooling. The solid content concentration at the time of stopping the polymerization was 39.3%. Below, the conditions described in Table 1 were set, and other than that, the resin powder 11 of PVA11 was obtained in the same manner as in Example 1.

[0209] [Example 12]

[0210] Polymerization and saponification were carried out in the same manner as in Example 2 described in Japanese Patent Application Publication No. 2019-011282 to obtain a coarse powder of ethylene-modified PVA (PVA12) having a degree of polymerization of 1850, a degree of saponification of 98.5 mol %, and an ethylene unit content of 6 mol %. The following conditions were set as shown in Table 1, and except for this, a resin powder 12 of PVA12 was obtained in the same manner as in Example 1.

[0211] [Example 13]

[0212] In a 250L reactor having a stirrer, a reflux condenser, a nitrogen inlet, a comonomer addition port, and an initiator addition port, 112.5kg of vinyl acetate, 37.5g of methanol (75% by mass of vinyl acetate: 25% by mass of methanol), and 220ml of a methanol solution in which methyl methacrylate was dissolved at 24% by mass were added, and nitrogen bubbling was performed while nitrogen substitution in the system was performed for 30 minutes. The temperature of the reactor was started to rise, and when the internal temperature reached 60°C, 35g of 2,2'-azobisisobutyronitrile (AIBN) was added to start polymerization, and 11L of the methanol solution of methyl methacrylate was added successively. When the polymerization rate reached 40%, the polymerization was stopped by cooling. The solid content concentration at the time of stopping the polymerization was 28.0%. Below, the conditions described in Table 1 were set, and except for this, the resin powder 13 of PVA13 was obtained in the same manner as in Example 1.

[0213] [Example 14]

[0214] A resin powder 14 of PVA14 was obtained in the same manner as in Example 2 except that the pulverization time by the pulverizer was shortened to 2 minutes and the pulverization was performed more coarsely than in Example 1.

[0215] [Examples 17 to 19]

[0216] Resin powder 17 of PVA17 and the like were obtained in the same manner as in Example 2 except that the surface processing was performed by the apparatus described in Table 1 instead of the Rocky mixer.

[0217] [Example 20]

[0218] The same method as in Example 2 was carried out except that the pulverization time by the pulverizer was extended to 10 minutes to make the powder finer than that in Example 1 and that the surface processing by the Lodge mixer was not performed, thereby obtaining a resin powder 20 of PVA20 and the like.

[0219] [Comparative Example 1]

[0220] A resin powder 1 ′ of PVA 1 ′ was obtained in the same manner as in Example 2 except that the pulverization time by the pulverizer was shortened to 1 minute and the pulverization was performed more coarsely than in Example 14.

[0221] [Comparative Example 2]

[0222] A resin powder 2' of PVA 2' was obtained in the same manner as in Example 2 except that the surface processing using the Rocky mixer was not performed.

[0223] Table 2 shows the polymerization degree and saponification degree of each PVA obtained in Examples 1 to 20 and Comparative Examples 1 to 2, the average roundness, average particle size and content of particles with a particle size of 100 to 1,000 μm of each resin powder, and the product of the average roundness and saponification degree.

[0224] [evaluate]

[0225] The angle of repose after humidity control was measured for each resin powder obtained in Examples 1 to 20 and Comparative Examples 1 to 2 by the above method in an atmosphere of 20° C. and 30% humidity and 20° C. and 65% humidity.

[0226] Table 3 shows the solubility of each resin powder obtained in Examples 1 to 20 and Comparative Examples 1 to 2 in water / NMP, the electrode uniformity (electrode homogeneity) when used as an electrode binder for each electrical storage device, and the electrical storage device characteristics.

[0227]

[0228]

[0229]

[0230] As shown in Table 3, when the resin powders of Examples 1 to 20 are used as binders, gel-like agglomerations are unlikely to occur when dissolved in water or NMP, thereby obtaining uniform electrodes, and as a result, batteries having high discharge capacity and low DC resistance are obtained. On the other hand, when the resin powders of Comparative Example 1 having a large average particle size and the resin powders of Comparative Example 2 having a small average roundness are used as binders, gel-like agglomerations are likely to occur when dissolved in water or NMP, and as a result, the uniformity of the electrode is impaired, the discharge capacity is reduced, and the DC resistance is increased.

Claims

1. An adhesive comprising a water-soluble resin powder, The water-soluble resin powder is composed of particles having an average particle size of 100 to 2,000 μm. For 50 particles randomly selected from particles having a particle size of 100 to 1,000 μm contained in the water-soluble resin powder, the average value PA of the roundness P of each particle represented by the following formula (1) is 0.1 to 0.8, [Number 1] In formula (1), r i is the radius of curvature of each corner of the particle, R is the radius of the largest inscribed circle of the particle, N is the number of corners a particle has, in, When the number of corners of a particle is 9 or more, the curvature radii of the 8 corners are adopted in ascending order of the curvature radii, and N is set to 8.

2. The adhesive according to claim 1, wherein The water-soluble resin is a vinyl alcohol polymer.

3. The adhesive according to claim 2, wherein: The viscosity average polymerization degree of the vinyl alcohol polymer is 200 to 5,000, and the saponification degree is 35 to 99.99 mol %.

4. The adhesive according to any one of claims 1 to 3, which satisfies the following formula (2): PA×S≥18 (2) In formula (2), PA is the average value of the roundness P, S is the saponification degree of the vinyl alcohol polymer (mol %), The average particle size of the water-soluble resin powder is 100 to 1,000 μm.

5. The adhesive according to any one of claims 1 to 3, wherein The water-soluble resin powder has a content of particles having a particle size of 100 to 1,000 μm of 50% by mass or more. 6 . An electrical storage device electrode comprising the binder according to claim 1 . 7 . A binder solution for electrical storage device electrodes, comprising the binder according to claim 1 and water. 8 . The binder solution for electrical storage device electrodes according to claim 7 , comprising N-methyl-2-pyrrolidone. 9 . A slurry for electrical storage device electrodes comprising the binder solution for electrical storage device electrodes according to claim 7 or 8 and an active material.

10. The electrical storage device electrode slurry according to claim 9, wherein The content of the binder is 0.1 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the active material. 11 . An electrical storage device electrode comprising a solidified body of the electrical storage device electrode slurry according to claim 9 or 10 and a current collector. 12 . An electric storage device comprising the electric storage device electrode according to claim 11 .

13. The method for producing the adhesive according to any one of claims 1 to 5, comprising: A step of obtaining a coarse powder of the water-soluble resin by pulverizing a resin solid containing the water-soluble resin; and A step of processing the surfaces of particles constituting the coarse powder.

Citation Information

Patent Citations

  • Binder containing vinyl alcohol polymer, slurry, nonaqueous electrolyte secondary battery, and its electrode

    JP1999250915A

  • Method for manufacturing positive electrode plate

    JP2013037955A

  • Binder composition for secondary battery electrode, secondary battery electrode, and secondary battery

    JP2017059527A

  • Positive electrode active material for nonaqueous electrolyte secondary battery, and method for producing the same, and nonaqueous electrolyte secondary battery

    JP2017107827A

  • Agricultural chemical binder, agricultural chemical granular composition, and manufacturing method therefor

    JP2019011282A